2006
DOI: 10.3748/wjg.v12.i26.4161
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and immunohistochemical analysis of gastrointestinal stromal tumor

Abstract: GIST has complicated arrangements and various cell types. Positivity of CD117 and CD34 is the most valuable factor in diagnosing GIST. Expression of p21WAF1 and Bax plays an important role in potential malignancy and malignancy rather than in benign GIST. p21WAF1 and Bax may be used as the markers in the assessment of GIST malignant potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Liu et al (12) revealed that CD117 (c-kit) and CD34 showed diffuse strong positive expressions in GISTs, and the positive rates were 98.1% and 92.3% of the GISTS in that study. Rabin et al (11) reported 40% to 70% of GIST's were positive for CD34, 20% to 30% were positive for SMA, 10% were positive for S100 protein and <5% were positive for desmin.…”
Section: Discussionmentioning
confidence: 61%
“…Liu et al (12) revealed that CD117 (c-kit) and CD34 showed diffuse strong positive expressions in GISTs, and the positive rates were 98.1% and 92.3% of the GISTS in that study. Rabin et al (11) reported 40% to 70% of GIST's were positive for CD34, 20% to 30% were positive for SMA, 10% were positive for S100 protein and <5% were positive for desmin.…”
Section: Discussionmentioning
confidence: 61%
“…However, this marker is also expressed in a large number of other tumours including melanoma, dermatofibrosarcoma, rhabdomyosarcoma and large cell lymphoma 27. Approximately 60–80% of GISTs are immunopositive for CD34, malignant tumours showing a slightly lower frequency than benign ones, and site specificity being increasingly recognised in terms of low expression in small bowel tumours and high expression in colorectal and oesophageal tumours 28 29. GISTs, therefore, appear to be the only Kit+CD34+vimentin+ cell in the gut 28.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60–80% of GISTs are immunopositive for CD34, malignant tumours showing a slightly lower frequency than benign ones, and site specificity being increasingly recognised in terms of low expression in small bowel tumours and high expression in colorectal and oesophageal tumours 28 29. GISTs, therefore, appear to be the only Kit+CD34+vimentin+ cell in the gut 28. Other markers include smooth muscle actin, which may be present in approximately 20–40% of GIST tumours, S-100 protein, which is positive in fewer than 5% of GISTs, and Desmin, positivity being rare, occurring principally in a focal fashion in only 1–2% of cases 3 28…”
Section: Discussionmentioning
confidence: 99%
“…Coexistence of the other neoplasm as a prognostic factor for survival in patients with GISTs has been not described in the literature. There are many reports regarding the occurrence, epidemiology, clinicopathology, immunohistochemical analysis and treatment of GISTs coexisting with other malignant neoplasms [33,40,45,46,47,48,49]. The survival rate between patients receiving surgery for only GIST and GIST coexisting with the other malignant neoplasm has not been described in the literature.…”
Section: Discussionmentioning
confidence: 99%